Evaluation of the nutritional status of sleeve gastrectomy patients: A prospective randomized clinical trial nutrition, eating behaviors before and after bariatric surgery - Erdem, Nihal Zekiye; Dallı Şen, Seher (Springer, 2022)
[Abstract Not Available]
Keywords: Gastrectomy Patients; Bariatric Surgery; Randomized